TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI IKAN DENGAN SISTEM PANCING: Studi Kasus Di Pemancingan Andalan Jaya Dan Kampung Batik Di Kecamatan Tamanan Kabupaten Bondowoso - Mohammad Firmansyah; Qurrotun A’yuni (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
In the practice of buying and selling, people sometimes ignore things that could be detrimental to each other. The loss is related to the object or to the property. This loss is due to ignorance or obscurity of the sale and purchase. Buying and selling fish in Tamanan District, Bondowoso Regency, namely buying and selling that contains elements of ambiguity (gharar) for objects that have been traded. Neither the seller nor the buyer can confirm the form of the object being traded based on the purpose of the contract, namely the sale and purchase of fish using the "fishing line" system. There are two issues studied in this thesis, namely (1) How is the Practice of Buying and Selling Fish with a Fishing System in Tamanan District, Bondowoso Regency. (2) What is the Review of Sharia Economic Law on the Sale and Purchase of Fish with a Fishing System in Tamanan District, Bondowoso Regency. The purpose of this study is to find out the Practice of Buying and Selling Fish with a Fishing System in Tamanan District, Bondowoso Regency, and to find out the Review of Sharia Economic Law on the Buying and Selling of Fish with a Fishing System. The author uses field research (field research). This research is a qualitative research then the data is described. This research is a research that describes objects systematically. Data and data sources used in this study are primary data sources and secondary data sources. Data collection techniques using observation and interviews. The results of this study indicate that (1) the practice of buying and selling fish using a fishing rod system which pays in advance at a price determined by the pond owner, (2) in terms of Sharia Economic Law on buying and selling fish with an illegal fishing system , there is an element of Gharar (unclear) in the object and subject of the pillars of sale and purchase so that it has the potential to cause harm to one of the parties.